Correlation of Muscular Leg Explosion Power Toward Short Distance Running Speed 100 Meters - Raffly Henjilito (JUARA : Jurnal Olahraga, 2019)
Judging from anatomical and physiological, in a sprint of 100 meters, feet have a muscle structure that is larger and longer than the other muscles. The foot is the body organ that has the most muscle and is a barrier to body weight and is one of the organs that functions as a balance. The purpose of this study was to determine the degree or strength of the relationship, shape or causal relationship and the reciprocal relationship between explosive limb muscle power with running the short distance of 100 Meters. The research method used in this study is a quantitative approach, a survey method with measurement and test techniques, while the analysis technique uses a correlation analysis approach that is a way to find out whether or not there is a relationship between variables. Testing the hypothesis of the relationship of limb muscle explosive power with running the short distance of 100 Meters of 0.659. The results of the study concluded that there was a significant correlation between leg muscle explosive power and 100 meter short distance running.